Socialization of Public Transport use in SMA Negeri 1 Kediri Tabanan Bali - Efendhi Prih Raharjo; Dwi Wahyu Hidayat; Ni Ketut Nova Ariani; I Wayan Arnaya; I Made Sukmayasa; Ida Ayu Masyuni; I Wayan Yudi martha Wiguna (Jurnal Pengabdian Kepada Masyarakat Semangat Nyata Untuk Mengabdi (JKPM Senyum), 2022)
Public transportation is one type of transportation mode that concerns many people's lives. However, the use of public transportation, especially in Indonesia, is currently very minimal. This is caused by the increase in the number of private vehicles that exceed the limit it often causes problems, especially traffic problems such as congestion. People who have private vehicles such as motorbikes, or cars, or can use taxis will rarely take public transportation. Those who have no choice but to take public transportation have a desire to own a private vehicle. If they can buy a private vehicle, they will no longer depend on public transportation. It is feared that if this is allowed to happen, the existence of public transportation may gradually fade away. Based on this, it is clear that socialization on public transportation is needed to provide knowledge about the use of public transportation.